Análise de culturas energéticas oleaginosas para produção de biodiesel no território de Irecê no semi-árido baiano - Lopes, Juliano da Silva (2010)
In this work are analyzed and displayed oilseeds more appropriate for the participation of family farming in the Territory of Irecê PNPB, from the dimensions of the sustainability of biodiesel from vegetable oils and social environmental and economic aspects, focusing on the first. It is proposed to establish a Pilot Program Planning Irecê Biodiesel (Biodiesel Pilot). The methodology for this research, classified as exploratory, was the collection of bibliographic data and documents and direct observation. The work is divided into three stages. In the first step we analyzed the integration of national and state policies for biodiesel in the Territory of Irecê policy for biodiesel as a component of energy sustainability and social inclusion and performance of family farms in the process. In the second step we analyze the characteristics and local conditions of each oilseed crop and participation of family farming in PNPB. The third step contains a model for analysis of oilseeds for biodiesel, and its application, through which we analyzed the soybean cotton, rapeseed and sunflower as alternatives for biodiesel production in the Territory of Irecê. The real difficulties in using some oilseeds are strongly associated with lack of information and a policy that prioritizes Agroenergy regionalized using local natural resources. The castor bean and sunflower oil are the most appropriate alternatives for supply on family farms in the Territory of Irecê for biodiesel production under PNPB.